Comparing the American and European diagnostic guidelines for cystic fibrosis: same disease, different language?. Issue 7 (15th April 2012) - Ooi, Chee Y; Dupuis, Annie; Ellis, Lynda; Jarvi, Keith; Martin, Sheelagh; Gonska, Tanja; Dorfman, Ruslan; Kortan, Paul; Solomon, Melinda; Tullis, Elizabeth; Durie, Peter R
Abstract : Background: The American and European cystic fibrosis (CF) guidelines recommend different diagnostic criteria. This study assessed diagnostic concordance between these recommendations. Methods: Subjects with single organ manifestations suggestive of CF (chronic sinopulmonary disease (RESP), chronic/recurrent pancreatitis (PANC) or obstructive azoospermia (AZOOSP)) were prospectively evaluated by sweat test, nasal potential difference and genotyping. Concordance in diagnostic outcomes between the two algorithms was measured using observed agreement and κ statistics. Results: A total of 208 subjects were evaluated. Observed agreement was 84.8% and level of agreement was excellent (κ=0.87) between the American and European recommendations. The RESP phenotype was associated with the highest degree of concordance (observed agreement ≥90%, κ=0.92) compared with the PANC (observed agreement 86%, κ=0.65) and AZOOSP (observed agreement 80%, κ=0.87) phenotypes. Incorporation of nasal potential difference into the American algorithm failed to improve the overall degree of concordance (good agreement level; κ=0.75); the level of agreement was unchanged in RESP and PANC subjects, but reduced in AZOOSP subjects (from excellent to good). Extensive genotyping had limited clinical utility in the diagnosis of CF in both algorithms. Conclusions: Despite inconsistencies between the American and European diagnostic recommendations, concordance in diagnostic outcomes among subjects presenting with single organ manifestations of CF was good to excellent. These diagnostic guidelines provide guidance and promote rigorous evaluation for the diagnosis of CF but neither guideline should be regarded as dogma.